Using participatory action research methods to address epistemic injustice within mental health research and the mental health system - Mooney, Roisin; Dempsey, Clair; Brown, Brian J.; Keating, Frank; Joseph, Doreen; Bhui, Kamaldeep (Frontiers in Public Health, 2023)
In this paper, we describe a model of research practise that addresses epistemic injustice as a central objective, by valuing lived experience and addressing structural disadvantages. We set out here the processes we undertook, and the experiences of those involved in an attempt to transform research practise within a study known as Co-pact. We do not discuss the findings of the research. Rather, we wish to build expertise on how to address epistemic injustice and offer examples of participatory research processes, central values, and practical procedures that we implemented.